A nano-modified polyvinyl butyral composite material, a preparation method and application thereof

By introducing organic nano-montmorillonite and organosilicon/fluorine additives for physical modification, the hygroscopicity and adhesion problems of PVB materials are solved, and the water resistance and thermal stability of the materials are improved, making them suitable for a variety of composite material applications.

CN123042452APending Publication Date: 2026-11-06EVERLIGHT YEAR POLYMER MATERIALS (JIANGSU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611369311.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing polyvinyl butyral (PVB) materials are prone to volume expansion and increased haze due to high hygroscopicity. They are also prone to delamination in humid and hot environments and tend to stick together during processing, affecting efficiency. Existing modification solutions pose risks of odor and yellowing.

Method used

By employing organic nano-montmorillonite and organosilicon/fluorine-based additives, the water resistance, anti-blocking properties, and thermal stability of PVB materials are improved through a physical modification mechanism, avoiding the use of specific chemical reaction additives.

Benefits of technology

It significantly improves the water resistance, anti-blocking properties and thermal stability of PVB composite materials, reduces raw material costs, conforms to the trend of green environmental protection, and is suitable for glass interlayer, artificial leather surface layer, waterproof fabric coating and printing base film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123042452A_ABST
    Figure CN123042452A_ABST
Patent Text Reader

Abstract

This invention relates to the field of polymer materials technology, and in particular to a nano-modified polyvinyl butyral composite material, its preparation method, and its application. The composite material comprises 100 parts of a PVB-based composite material, 1-10 parts of organic nano-montmorillonite, 0.1-3 parts of an anti-blocking modifier, and 0.1-2 parts of a compounded antioxidant. The PVB-based composite material contains PVB resin and a plasticizer. The organic nano-montmorillonite is obtained by modifying sodium-based montmorillonite with a quaternary ammonium salt surfactant. This invention significantly improves the water resistance, anti-blocking properties, and thermal stability of PVB materials by introducing organic nano-montmorillonite (OMMT) and organosilicon / fluorine-based additives, without using restricted patented additives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and in particular to a nano-modified polyvinyl butyral composite material, its preparation method, and its application. Background Technology

[0002] Polyvinyl butyral (PVB) has become the standard material for interlayers in safety glass due to its excellent optical transparency, adhesive strength, and flexibility, and is widely used in fabric coatings, printed base films, and other fields. However, the large number of hydroxyl groups remaining on the PVB resin molecular chain results in significant hygroscopicity, which not only causes material volume expansion and increased haze, but also leads to delamination of laminated products in humid and hot environments. Furthermore, PVB melt is prone to sticking during processing and storage, affecting the efficiency of downstream processes.

[0003] To address the aforementioned issues, existing technologies, such as EP 4269092 A1, "A Modified Polyvinyl Butyral Material and Its Preparation and Application," propose complex additive systems, including specific combinations of crystalline aluminum silicate fillers, carbodiimide anti-hydrolysis agents, zinc / calcium stearate lubricants, tetramethylthiuram monosulfide (TMTM), and trimethylolpropane tris(3-mercaptopropionate) (TMPTMP). While this approach improves performance to some extent, some of its sulfur-containing additives (such as TMTM) pose a potential risk of off-odor and yellowing.

[0004] Therefore, developing a high-performance PVB composite material that can utilize physical modification mechanisms rather than specific chemical reactions has become an urgent problem for the industry. Summary of the Invention

[0005] The purpose of this invention is to provide a nano-modified polyvinyl butyral composite material, its preparation method and application. By introducing organic nano-montmorillonite (OMMT) and organosilicon / fluorine additives, the water resistance, anti-blocking and thermal stability of PVB materials are significantly improved without using restricted patented additives.

[0006] To achieve the above objectives, the present invention provides a nano-modified polyvinyl butyral composite material, comprising 100 parts of PVB-based composite material, 1-10 parts of organic nano-montmorillonite, 0.1-3 parts of anti-sticking modifier, and 0.1-2 parts of compounded antioxidant. The PVB-based composite material contains PVB resin and plasticizer, and the organic nano-montmorillonite is obtained by modifying sodium-based montmorillonite with quaternary ammonium salt surfactant.

[0007] Preferably, the quaternary ammonium salt surfactant is bis(octadecyldimethylammonium chloride) or hexadecyltrimethylammonium bromide.

[0008] Preferably, the anti-sticking modifier is selected from one or more of polymethylsilsesquioxane micro powder, polydimethylsiloxane micro powder, and polytetrafluoroethylene micro powder.

[0009] Preferably, the compound antioxidant is composed of hindered phenolic primary antioxidant and phosphite secondary antioxidant in a mass ratio of 1:(1-3).

[0010] Preferably, the hindered phenolic primary antioxidant is one of antioxidant 1010 and antioxidant 1076; the phosphite secondary antioxidant is one of antioxidant 168 and antioxidant 626.

[0011] Preferably, the plasticizer is selected from one or more of aliphatic diester plasticizers, phthalate plasticizers, polyol ester plasticizers, and phosphate ester plasticizers.

[0012] Preferably, it also includes 1 to 8 parts of hydrophobic nano-silica, which are fumed silica nanoparticles with an average particle size of 10-30 nm after surface hydrophobic treatment with hexamethyldisilazane.

[0013] This invention also provides a method for preparing the above-mentioned nano-modified polyvinyl butyral composite material, comprising the following steps: S1. Premixing: PVB-based composite material, organic nano-montmorillonite, anti-sticking modifier, and compound antioxidant are premixed in a high-speed mixer at 800-1500 rpm for 3-5 minutes to obtain premixed material; S2, Melt Blending: The premixed material from S1 is added to a twin-screw extruder and melt-blended and extruded under a temperature gradient of 140~180℃, with a screw speed of 100~400rpm, to obtain an extruded melt; S3. Filtration and granulation: After the extruded melt of S2 is filtered through an 80-150 mesh sieve to remove impurities, it is then water-cooled, air-dried, and pelletized to obtain nano-modified polyvinyl butyral composite material granules.

[0014] Preferably, in S1, hydrophobic nano-silica is also added to the high-speed mixer; in S2, the temperature gradient of the twin-screw extruder is set as follows: feeding section 140-150℃, melting section 160-170℃, homogenization section 170-180℃.

[0015] The present invention also provides a nano-modified polyvinyl butyral composite material for preparing glass interlayers, artificial leather surface layers, waterproof fabric coatings, or printing base films.

[0016] Therefore, the present invention, employing the above-mentioned nano-modified polyvinyl butyral composite material, its preparation method, and its application, has the following beneficial effects: (1) The present invention utilizes the synergistic effect of the nanobarrier effect of organic nano-montmorillonite and the surface migration effect of low surface energy anti-adhesion modifier to replace the specific chemical reaction system in the prior art with a physical modification mechanism, thereby improving the water resistance, anti-adhesion, thermal stability, processing fluidity and optical properties of PVB composite material. (2) The formula of this invention is compatible with recycled PVB materials (such as recycled PVB materials obtained by crushing, flotation and drying of recycled PVB laminate film), which can effectively realize the resource reuse of waste PVB laminate products and reduce raw material costs. At the same time, it does not contain sulfur, heavy metals and halogen-restricted additives, avoiding the release of odors and yellowing problems during the processing, and the product is more in line with the green and environmentally friendly trend.

[0017] (3) The preparation method provided by the present invention only requires three core steps: premixing, melt blending extrusion, and filtration granulation. It is fully compatible with existing general twin-screw extrusion equipment and casting / calendering processing equipment. It does not require large-scale equipment modification or process innovation. The overall preparation process is short, efficient, and cost-controllable, making it suitable for rapid promotion and application in existing polymer processing enterprises.

[0018] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0019] Figure 1 This is a process flow diagram of a method for preparing a nano-modified polyvinyl butyral composite material according to Embodiment 1 of the present invention. Detailed Implementation

[0020] This invention provides a nano-modified polyvinyl butyral composite material, comprising 100 parts of PVB-based composite material, 1-10 parts of organic nano-montmorillonite, 0.1-3 parts of anti-sticking modifier, and 0.1-2 parts of compounded antioxidant. The PVB-based composite material contains PVB resin and plasticizer, and the organic nano-montmorillonite is obtained by modifying sodium-based montmorillonite with quaternary ammonium salt surfactant.

[0021] The nano-modified polyvinyl butyral composite material of the present invention, through the synergistic effect of the nanosheet barrier effect of organic nano-montmorillonite and the low surface energy migration effect of the anti-sticking modifier, significantly reduces the water absorption rate and surface friction coefficient of the material without relying on tetramethylthiuram monosulfide, trimethylolpropane tris(3-mercaptopropionate), zinc stearate and calcium stearate. At the same time, it improves thermal stability and processing fluidity, and has excellent anti-blocking properties, optical transparency and environmental resistance. It is suitable for casting films, calendered sheets and laminated products.

[0022] Preferably, the PVB resin is recycled PVB material obtained by crushing, flotation to remove impurities, and drying recycled PVB laminate film, with a hydroxyl content of 15-20 wt% and a number average molecular weight of 50,000-200,000. This realizes the resource-based reuse of waste PVB laminate products, effectively reduces raw material costs, and reduces solid waste emissions.

[0023] Preferably, the quaternary ammonium salt surfactant is bis(octadecyldimethylammonium chloride) or hexadecyltrimethylammonium bromide.

[0024] This invention utilizes sodium-based montmorillonite, which is modified with quaternary ammonium salt surfactants and organic cations (such as dioctadecyl dimethyl ammonium chloride) to replace sodium ions between montmorillonite layers, increasing the interlayer spacing (≥2.0 nm) and imparting hydrophobicity to the sheets. In a PVB matrix, the organic nano-montmorillonite can be exfoliated into nanoscale sheets, significantly extending the penetration path of water molecules through a "maze effect," thereby greatly improving the water-blocking performance of the composite material. Simultaneously, the barrier effect of the nanosheets on gases and heat also helps improve the thermal stability of the material.

[0025] The preferred option is that the interlayer spacing of the organic nano-montmorillonite is ≥2.0 nm.

[0026] The organic nano-montmorillonite of this invention can be exfoliated into nanoscale sheets in a PVB matrix, extending the penetration path of water molecules through the "maze effect".

[0027] Preferably, the anti-sticking modifier is selected from one or more of polymethylsilsesquioxane (PMSQ) micro powder, polydimethylsiloxane micro powder, and polytetrafluoroethylene (PTFE) micro powder.

[0028] The anti-stick modifier of the present invention has extremely low surface energy and can migrate to the material surface during processing to form a lubricating layer, so that the obtained nano-modified polyvinyl butyral composite material has excellent anti-stick properties. It is not easy to self-stick or stick to the equipment during storage and subsequent processing (such as winding and lamination), and does not affect the optical transparency and flexibility of the material itself. It is particularly suitable for preparing products that require long-term anti-stick properties, such as glass interlayer film and waterproof fabric coating.

[0029] Preferably, the compound antioxidant consists of a hindered phenolic primary antioxidant and a phosphite secondary antioxidant in a mass ratio of 1:(1-3). The hindered phenolic primary antioxidant, as the primary antioxidant, can efficiently capture polymeric free radicals and interrupt the oxidation chain reaction; the phosphite secondary antioxidant, as an auxiliary antioxidant, can reduce hydroperoxides to stable alcohols, preventing their decomposition into free radicals. The interaction between the two produces a significant "synergistic effect," providing more durable protection against oxidative degradation and thermo-oxidative aging of PVB during high-temperature processing and long-term use compared to a single antioxidant. The resulting composite material exhibits a higher thermal decomposition temperature (Td5% increase), better resistance to yellowing, and better long-term heat resistance, ensuring the service life and appearance quality of the composite material under harsh environments.

[0030] Preferably, the hindered phenolic primary antioxidant is one of antioxidant 1010 and antioxidant 1076; the phosphite secondary antioxidant is one of antioxidant 168 and antioxidant 626.

[0031] Preferably, the plasticizer is selected from one or more of aliphatic diester plasticizers, phthalate plasticizers, polyol ester plasticizers, and phosphate ester plasticizers.

[0032] Preferably, the composite material also includes 1-8 parts of hydrophobic nano-silica, which are fumed silica nanoparticles treated with hexamethyldisilazane for hydrophobicity, with an average particle size of 10-30 nm. The hydrophobically treated nano-SiO2 contains hydrophobic groups on its surface, resulting in better compatibility with the PVB matrix. It can be uniformly dispersed in the composite material and form physical cross-linking points, effectively transferring and sharing external stress, thereby improving mechanical strength. At the same time, the nano-SiO2 particles have high hardness and can act as a microscopic "rigid wear-resistant skeleton," preferentially bearing wear when the composite material surface is subjected to friction. Furthermore, the hydrophobic layer can reduce the plasticizing damage of water molecules to the interface, thus significantly improving the wear resistance of the composite material.

[0033] This invention also provides a method for preparing the above-mentioned nano-modified polyvinyl butyral composite material, comprising the following steps: S1. Premixing: PVB-based composite material, organic nano-montmorillonite, anti-sticking modifier, and compound antioxidant are premixed in a high-speed mixer at 800-1500 rpm for 3-5 minutes to obtain premixed material; S2, Melt Blending: The premixed material from S1 is added to a twin-screw extruder and melt-blended and extruded under a temperature gradient of 140~180℃, with a screw speed of 100~400rpm, to obtain an extruded melt; S3. Filtration and granulation: After the extruded melt of S2 is filtered through an 80-150 mesh sieve to remove impurities, it is then water-cooled, air-dried, and pelletized to obtain nano-modified polyvinyl butyral composite material granules.

[0034] Preferably, in S1, hydrophobic nano-silica is also added to the high-speed mixer; in S2, the temperature gradient of the twin-screw extruder is set as follows: feeding section 140-150℃, melting section 160-170℃, homogenization section 170-180℃.

[0035] The present invention also provides a nano-modified polyvinyl butyral composite material for preparing glass interlayers, artificial leather surface layers, waterproof fabric coatings, or printing base films.

[0036] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.

[0037] The organic nano-montmorillonite used in this invention embodiment is prepared by the following steps: sodium-based montmorillonite is dispersed in deionized water to prepare a suspension with a mass fraction of 2%, and heated to 75°C; a quaternary ammonium salt surfactant (bis(octadecyldimethylammonium chloride) or hexadecyltrimethylammonium bromide) is weighed at 1.2 times the cation exchange capacity of montmorillonite, dissolved in an ethanol aqueous solution, and slowly added dropwise to the suspension, and stirred at a constant temperature for 5 hours; after the reaction is completed, the mixture is filtered, and the filter cake is washed with deionized water until no chloride ions are detected (using 0.1 mol / L AgNO3 solution); finally, it is vacuum dried and pulverized at 80°C, and passed through a 200-mesh sieve to obtain organic nano-montmorillonite with an interlayer spacing of 2.5 nm.

[0038] The hydrophobic nano-silica used was prepared by the following steps: fumed silica nanoparticles (average particle size 20 nm) were placed in a high-speed mixer and heated to 110 °C; hexamethyldisilazane was added at 10% of the silica mass, and the mixture was stirred at 1000 rpm for 45 min under nitrogen protection; then the temperature was raised to 155 °C and the treatment continued for 1.5 h to allow the surface hydroxyl groups to fully react with hexamethyldisilazane, thus completing the hydrophobic modification; finally, the mixture was cooled and sieved to obtain hydrophobic nano-silica with a contact angle ≥110°.

[0039] Example 1 A nano-modified polyvinyl butyral composite material comprises 100 parts of a PVB-based composite material (90 parts of recycled PVB material, 18% hydroxyl content, and 10 parts of di(2-propylheptyl) phthalate plasticizer), 10 parts of organic nano-montmorillonite (sodium montmorillonite modified with bis(octadecyldimethylammonium chloride, interlayer spacing 2.5 nm), 1 part of polymethylsilsesquioxane micropowder (average particle size 3 μm), 0.5 parts of a compounded antioxidant (antioxidant 1010: antioxidant 168 = 1:2 by mass), and 3 parts of hydrophobic nano-silica (average particle size 20 nm). The preparation method is as follows: Figure 1 As shown, it includes the following steps: S1. Premixing: PVB-based composite material, organic nano-montmorillonite, polymethylsilsesquioxane micro powder, compound antioxidant, and hydrophobic nano-silica are premixed in a high-speed mixer at 1200 rpm for 4 min to obtain premixed material.

[0040] S2, Melt Blending: The premixed material from S1 is added to a twin-screw extruder for melt blending and extrusion. The screw speed is 300 rpm, and the temperature gradient of the twin-screw extruder is set as follows: 150°C for the feeding section, 165°C for the melting section, and 175°C for the homogenization section, to obtain the extruded melt.

[0041] S3. Filtration and granulation: After the extruded melt of S2 is filtered through a 120-mesh sieve to remove impurities, it is then water-cooled, air-dried, and pelletized to obtain nano-modified polyvinyl butyral composite material granules.

[0042] Example 2 The difference from Example 1 is that no hydrophobic nano-silica was added; otherwise, they are the same as in Example 1.

[0043] Example 3 The difference from Example 1 is that the anti-sticking modifier is polytetrafluoroethylene micro powder, while the rest is the same as in Example 1.

[0044] Comparative Example 1 A modified polyvinyl butyral composite material comprises 100 parts of a PVB-based composite material (90 parts of recycled PVB material, 18% hydroxyl content, 10 parts of di(2-propylheptyl) phthalate plasticizer), 12.5 parts of kaolin, 2 parts of carbodiimide, 2.8 parts of zinc stearate, 0.7 parts of calcium stearate, 0.12 parts of tetramethylthiuram monosulfide (TMTM), 0.003 parts of trimethylolpropane tris(3-mercaptopropionate) (TMPTMP), and 2.3 parts of porous silicate. Its preparation method includes the following steps: S1. Premixing: PVB-based composite material is premixed with kaolin, carbodiimide, zinc stearate, calcium stearate, tetramethylthiuram monosulfide (TMTM), trimethylolpropane tris(3-mercaptopropionate) (TMPTMP) and porous silicate in a high-speed mixer at 1200 rpm for 4 min to obtain premixed material.

[0045] S2 is the same as S2 in Example 1.

[0046] S3 is the same as S3 in Example 1.

[0047] Comparative Example 2 A polyvinyl butyral composite material, comprising 100 parts of a PVB-based composite material (90 parts of recycled PVB material, 18% hydroxyl content, and 10 parts of di(2-propylheptyl) phthalate plasticizer). Its preparation method includes the following steps: S1. Premixing: The PVB-based composite material is premixed in a high-speed mixer at 1200 rpm for 4 minutes to obtain the premixed material.

[0048] S2 is the same as S2 in Example 1.

[0049] S3 is the same as S3 in Example 1.

[0050] Performance testing The granules prepared in Examples 1-3 and Comparative Examples 1-2 were calendered at 180°C to form uniform films with a thickness of 0.2 mm. The resulting films were tested according to the following standards, and the results are shown in Table 1.

[0051] (1) Water absorption rate: Refer to GB / T 1034-2008 standard. Cut the film sample into 50mm×50mm square test pieces, dry them in an 80℃ vacuum oven to constant weight (dry until the difference between two consecutive weighings does not exceed 0.1mg), and record the dry weight m0. Completely immerse the dried test pieces in deionized water at 23℃, soak for 24 hours, remove them, quickly absorb the surface moisture with filter paper, and immediately weigh and record the wet weight m1. The water absorption rate is calculated according to the following formula: Water absorption rate (%) = (m1 - m0) / m0 × 100% Five parallel samples were tested for each formulation, and the arithmetic mean was taken as the final result.

[0052] (2) Anti-sticking property: Cut the film sample into 50mm×50mm square test pieces. Take two test pieces and place them face to face. Place a 3kg weight (approximately 60mm in diameter at the bottom) at the center of the upper surface of the stacked test pieces. Add a polytetrafluoroethylene film to the contact surface with the test pieces to prevent the weight from sticking. Place the assembled sample in a constant temperature hot air oven at 150℃ and let it stand for 120 hours. After cooling to room temperature, manually peel the two test pieces at a speed of approximately 50mm / min. Observe whether the two test pieces stick together. Pass (non-adhesive): The two test pieces can be separated smoothly and there are no visible residues on the surface after separation; Fail (adhesion): The two test pieces cannot be separated, tear during separation, or have adhesive residue remaining on the surface after separation.

[0053] (3) Thermal stability (TGA test): Refer to GB / T 27761-2011 standard. Thermogravimetric analysis is used for testing, and the temperature corresponding to the sample mass loss reaching 5% (Td5%) is recorded as the evaluation index of material thermal stability. The higher the Td5% value, the better the thermal stability of the material.

[0054] (4) Melt Flow Rate (MFR): Refer to GB / T 3682.1-2018 standard. The melt flow rate tester was used to test the melt flow rate at a temperature of 170℃ and a load of 2.16kg. Each formulation was tested 3 times, and the arithmetic mean was taken as the final result.

[0055] (5) Transmittance and haze: Refer to GB / T 2410-2016 standard. The transmittance / haze meter was used for testing at room temperature. Five parallel samples were tested for each formulation, and the arithmetic mean was taken as the final result.

[0056] Table 1 Test results of Examples 1-3 and Comparative Examples 1-2

[0057] Results Analysis: As shown in Table 1, all performance indicators of Examples 1-3 were superior to the blank control (Comparative Example 2). Among them, Example 1 showed the best overall performance, with a water absorption rate as low as 1.8%, and passed the stringent anti-sticking test. This indicates that the synergistic effect of the organic nano-montmorillonite and the anti-sticking modifier effectively compensated for the performance gap caused by the absence of metal soaps and thiuram compounds. Comparative Example 1 used the formulation of patent EP4269092A1, and its water absorption rate was reasonably controlled (2.5%), but it failed the anti-sticking test at 150℃ / 120h and showed slight yellowing at high temperatures (data not listed), verifying the limitations of this specific system in long-term heat resistance and anti-sticking. Comparative Example 2 was a blank control, without any modification, with a high water absorption rate (4.2%), making it extremely prone to adhesion and exhibiting poor thermal stability (Td5% only 310℃), which could not meet the requirements of practical applications.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A nano-modified polyvinyl butyral composite material, characterized in that: It includes 100 parts of PVB-based composite material, 1-10 parts of organic nano-montmorillonite, 0.1-3 parts of anti-sticking modifier, and 0.1-2 parts of compounded antioxidant. The PVB-based composite material contains PVB resin and plasticizer. The organic nano-montmorillonite is obtained by modifying sodium-based montmorillonite with quaternary ammonium salt surfactant.

2. The nano-modified polyvinyl butyral composite material according to claim 1, characterized in that: The quaternary ammonium salt surfactant is either dioctadecyldimethylammonium chloride or hexadecyltrimethylammonium bromide.

3. The nano-modified polyvinyl butyral composite material according to claim 1, characterized in that: The anti-sticking modifier is selected from one or more of polymethylsilsesquioxane micro powder, polydimethylsiloxane micro powder, and polytetrafluoroethylene micro powder.

4. The nano-modified polyvinyl butyral composite material according to claim 1, characterized in that: The compound antioxidant is composed of hindered phenolic primary antioxidant and phosphite secondary antioxidant in a mass ratio of 1:(1-3).

5. The nano-modified polyvinyl butyral composite material according to claim 4, characterized in that: The hindered phenolic primary antioxidant is one of antioxidant 1010 and antioxidant 1076; the phosphite secondary antioxidant is one of antioxidant 168 and antioxidant 626.

6. The nano-modified polyvinyl butyral composite material according to claim 1, characterized in that: The plasticizer is selected from one or more of the following: aliphatic diester plasticizers, phthalate plasticizers, polyol ester plasticizers, and phosphate ester plasticizers.

7. The nano-modified polyvinyl butyral composite material according to claim 1, characterized in that: It also includes 1 to 8 parts of hydrophobic nano-silica, which are fumed silica nanoparticles with an average particle size of 10-30 nm after being hydrophobically treated with hexamethyldisilazane.

8. The method for preparing a nano-modified polyvinyl butyral composite material according to any one of claims 1-7, characterized in that: Includes the following steps: S1. Premixing: PVB-based composite material, organic nano-montmorillonite, anti-sticking modifier, and compound antioxidant are premixed in a high-speed mixer at 800-1500 rpm for 3-5 minutes to obtain premixed material; S2, Melt Blending: The premixed material from S1 is added to a twin-screw extruder and melt-blended and extruded under a temperature gradient of 140~180℃, with a screw speed of 100~400rpm, to obtain an extruded melt; S3. Filtration and granulation: After the extruded melt of S2 is filtered through an 80-150 mesh sieve to remove impurities, it is then water-cooled, air-dried, and pelletized to obtain nano-modified polyvinyl butyral composite material granules.

9. The method for preparing a nano-modified polyvinyl butyral composite material according to claim 8, characterized in that: In S1, hydrophobic nano-silica was added to the high-speed mixer; in S2, the temperature gradient of the twin-screw extruder was set as follows: feeding section 140-150℃, melting section 160-170℃, homogenization section 170-180℃.

10. A nano-modified polyvinyl butyral composite material as described in any one of claims 1-7 is used to prepare a glass interlayer, an artificial leather surface layer, a waterproof fabric coating, or a printing base film.

Citation Information

Patent Citations

  • Modified polyvinyl butyral material, and preparation and applications thereof

    EP4269092A1